THE SELECTIVE INFLUENCE OF L- AND D-AMINO ACIDS ON THE BIOMEMBRANE (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
The influence of L-Val and D-Val amino acids on a phospholipid bilayer, which serves as a physical model for the cell membrane, has been studied using the simultaneous small and large angle X-ray diffraction, as well as optical polarizing microscopy methods. It is shown that despite L-Val and D-Val amino acids having the same structure and differing only on their chirality, the effect of L-amino acids and, consequently, their permeability on the membrane is greater than that of D one. This indicates that the cell membrane exhibits a certain selectivity towards chiral molecules. Additionally, it was demonstrated that the hydrophobicity and hydration of an L- and D-amino acids also play a significant role on the interaction between the amino acids and the cell membrane. It is known that L-amino acids are more prevalent in nature than D-amino acids. This research was to explore the interaction of L- and D-amino acids with the phospholipid bilayer, which can serve as a physical model of the biological membrane, aiming at understanding the differences of their effects. This could help to explain the widespread presence of L-amino acids in nature and the scarcity of D-amino acids. The data obtained in this work suggest that this difference is likely due to the distinct mechanisms of interaction between L- and D-amino acids with the bilayer. Investigating the interaction of these amino acids with the phospholipid bilayer, which forms the essential structure of biological membranes, one can gain insights into the mechanisms of their interaction with biological membranes.
Keywords: L-Val and D-Val amino acids; selective effects on phospholipid bilayer; chiral molecules; hydrophobicity